Clinical characteristics and risk factors of patients with cystic fibrosis-related diabetes and pre-diabetes: cohort of cystic fibrosis registry of Turkiye - Ozaslan, Mehmet Mustafa; Kartal Ozturk, Gokcen; Gulen, Figen; Demirdogen, Ezgi; Cobanoglu, Nazan; Tekin, Merve Nur; Dogru Ersoz, Deniz (Walter de Gruyter Gmbh, 2026)
Objectives Cystic fibrosis-related diabetes (CFRD) is the most common comorbidity in patients with cystic fibrosis (CF). This study aimed to determine the prevalence and risk factors of CFRD using data from the CF Registry of T & uuml;rkiye (CFRT). Methods All patients with CF who underwent diabetes screening in 2022 or earlier were included in the study. The clinical and demographic characteristics of patients with CFRD, pre-diabetes (impaired glucose tolerance, impaired fasting glucose, indeterminate glucose tolerance), and those with normal screening results (NSR) were compared. Results Of the 1,702 patients registered in the data system in 2022, 916 patients from 21 centers who underwent diabetes screening were included in the study. CFRD was diagnosed in 102 patients (11.2 %), there were 56 patients (6.1 %) with pre-diabetes, and NSR were found in 757 patients (82.7 %). The youngest patient diagnosed with diabetes was 6 years old. In patients with CFRD, the median age of patients was found to be higher (p<0.001), body mass index (BMI) was found to be lower (p 0.017); chronic Pseudomonas aeruginosa (P. aeruginosa) colonization (p<0.001), severe mutations (60.8 %, p<0.001), and pancreatic insufficiency (56.1 %, p<0.001) were more frequent; median FEV1% and FVC% values were significantly lower (p<0.001 and p<0.002, respectively) compared to non-diabetic patients. Conclusions CFRD is associated with impaired pulmonary function, poor nutritional status, and increased chronic bacterial colonization of the airways. Advanced age, decreased respiratory function, severe genotype, and pancreatic insufficiency are risk factors for CFRD.
Keywords: cystic fibrosis; diabetes; children